Continuous positive airway pressure can improve depression in patients with obstructive sleep apnoea syndrome: a meta-analysis based on randomized controlled trials. Issue 3 (March 2020) - Yang, Xiangli; Yang, Jun; Yang, Chunwei; Niu, Lin; Song, Fucun; Wang, Lin
Objective: Substantial research indicates a clear relationship between obstructive sleep apnoea syndrome (OSAS) and depression. The study aim was to quantitatively evaluate whether continuous positive airway pressure (CPAP) therapy improves mood symptoms in OSAS patients. Methods: PubMed and Embase databases were systematically searched up to 2017 for publications on the impact of CPAP on mood symptoms in OSAS patients. Results: For the final analysis, nine randomized controlled trials comprising 1, 052 patients were selected. The pooled standard mean difference (SMD) of the effect of CPAP on depression was 0.31 (95% confidence interval 0.18, 0.43). A subgroup analysis showed that when CPAP use was greater than 4 hours per night, it tended to be effective in improving patients' mood symptoms (SMD = 0.38; confidence interval 0.23, 0.54). Analysis of publication bias using Egger's test found no evidence of publication bias. Conclusion: CPAP treatment can improve depression in OSAS patients.